Social acceptability of government acquisition of private lands in high-risk areas case of Barangay Rizal Makati City - Tamayo, Maritess T. (School of Urban and Regional Planning,University of the Philippines Diliman, 2019)
A natural disaster is a natural process or phenomenon that may cause loss of life, injury or other health impacts, property damage, loss of livelihoods and services, social and economic disruption, or environmental damage. In recent years, discussions focused on the West Valley Fault which PHIVOLCS claims to be rip for a strong quake. Expected to generate a sounding 7.2 magnitude earthquake, the West Valley Fault (formerly known as Marikina Valley Fault System) is a 90-kilometer-long fault system that passes through various cities and provinces to include Bulacan, Quezon City, Marikina, Pasig, Makati, Taguig, Muntinlupa, Rizal, Cavite, and Laguna. In Makati City, four barangays are transected by the WVF and in view of the recent occurrences of earthquakes throughout the country, the City has started retagging lots to determine which households are within the buffer zone. The retagging will give an accurate data for the implementation of projects intended to increase awareness of the community and reduce/mitigate impacts. Strategies range from IEC's to stakeholders/barangay consultations, installation of WVF markers to possible acquisition of private lands located within 30 meters buffer zone. Under the city's zoning ordinance, the buffer zone should be converted into open spaces to avert disaster should a 7.2- magnitude earthquake be generated by the fault line's movement.In the case of Barangay Rizal, Makati City, the implementation of the urban redevelopment plan has been halted for many years due to inevitable changes in the stakeholders' participation, involvement and prioritization. Largely contributing to this is the planned clearing of the 15 meters easement on each side of the west valley fault trace, which calls for land acquisition. With the objective of determining the social acceptability of private land acquisition by the government, the study focused on the respondents' awareness on both the rights of the owners and of the government, their knowledge and understanding of the West Valley Fault and the MRSURP Project, and determined thei willingness to give up and sell their private lands to the government. A total of 242 respondents were considered for the study and they are from Zones 7,8,9,10, and 1 the WVF trace has been identified to pass through. Based on the data gathered and processed, the respondents are aware of both their rights and that of the government to acquire private lands, they understand the dangers and the risks they face living near the WVF and agree to the objectives of the project which is to make the community resilient, however they are very firm and not willing to give up their lands for either the safety of the majority or the payment of a just compensation.There is, therefore, the need to revisit the provisions of the proposed redevelopment plans and evaluate the proposed programs, Projects and Actions (PPA), in terms of implementations. PPAs that do not require government acquisition of land may be prioritized and those that require, be next in line while the government finalizes an offer which primarily covers payment of just compensation and relocation as top of mind conditions for the respondents. Meanwhile, the local government of Makati together with the Barangay, can continue holding WVF-related activities especially those that which make the community resilient, and the public more informed.